THE METHODOLOGY OF THE STUDY OF MEANINGFUL UNITS OF THE OFFICIAL DISCOURSE OF THE REPUBLICS – THE SUBJECTS OF THE RUSSIAN FEDERATION – ON THE ISSUES OF FORMING ALLRUSSIAN CIVIC IDENTITY - D. Yu. Znamenskiy; E. P. Kazban (Вестник университета)
The article deals with the method of analyzing the discourse of the republics (subjects of the Russian Federation) on national policy and the formation of the All-Russian civic identity. The author notes the importance of analyzing the positions of the republics as national subjects of the Russian Federation on the interpretation of the concept of All-Russian civic identity, as well as its relationship with the Republican or ethnic identity. The authors emphasize the potential of content analysis as the main research method in this particular case, which is explained by the possibility of quantifying the degree of attention of the Republican authorities to the issue under consideration, as well as identifying the attitude of regional elites and the media to it. At the same time, there is a need to verify the results of content analysis using qualitative methods, such as an expert focus group interview. Based on the results  of approbation of the developed research toolkit, the authors put forward three hypotheses that need to be  tested in the course of further study of the official discourse of the republics – subjects of Russian Federation  on the stated problems.